Applicability of the European Society of Cardiology Guidelines on the management of acute coronary syndromes to older people with haemophilia A – A modified Delphi consensus by the ADVANCE Working Group. Issue 1 (21st October 2022) - Klamroth, Robert; Ay, Cihan; De Moerloose, Philippe; Fontana, Pierre; Windyga, Jerzy; Astermark, Jan; Berntorp, Erik; Carvalho, Manuela; Dolan, Gerard; Hermans, Cedric; Holme, Pål Andre; Kenet, Gili; et al.
Abstract: Introduction: As people with haemophilia (PWH) receive better treatment and live longer they are more likely to encounter cardiovascular disease (CVD) and other comorbidities. ESC guidelines for the acute management of patients presenting with acute coronary syndrome (ACS) are based on the non‐haemophilia population. Aim: To review the guidelines and propose relevant adaptations for PWHA without inhibitors who are treated with prophylaxis and present with ACS. Methods: As part of the ADVANCE Group, 20 European haemophilia experts used a modified Delphi approach to develop and gain consensus on proposed adaptations of the ESC guidelines for PWHA without inhibitors. Results: Of the 32 Class I recommendations across both guidelines, adaptions were considered necessary and proposed for 15. The adaptions highlight the need to provide sufficient FVIII trough levels at the time of antithrombotic treatment in people with haemophilia A (HA) without inhibitors. Patients receiving emicizumab prophylaxis and requiring oral anticoagulation therapy or combined single antiplatelet plus oral anticoagulation therapy will require additional FVIII replacement therapy. Conclusion: In the absence of high‐quality clinical evidence, the combined expert opinion used to develop these adaptions to the current ESC guidelines may help to guide clinicians in their treatment decisions when a PWHA presents with ACS.